2021
DOI: 10.1186/s12866-021-02181-7
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro compatibility assay of indigenous Trichoderma and Pseudomonas species and their antagonistic activities against black root rot disease (Fusarium solani) of faba bean (Vicia faba L.)

Abstract: Background Faba bean (Vicia faba L.) cultivation is highly challenged by faba bean black root rot disease (Fusarium solani) in high lands of Ethiopia. To ensure sustainable production of faba beans, searching for eco-friendly disease management options is necessary to curb the progress of the disease timely. The indigenous biocontrol agents that suit local environments may effectively strive with in-situ microorganisms and suppress local pathogen strains. This study aimed to screen antagonistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
(41 reference statements)
1
20
0
Order By: Relevance
“… Padder and Sharma (2011) reported that culture filtrate of T. hamatum had a significant inhibitory effect on spore germination of Colletotrichum lindemuthianum , and the inhibitory activity of culture filtrates of Trichoderma sp. have also been reported against other fungal pathogens, including Fusarium solani ( Dugassa et al, 2021 ) and F. oxysporum ( Shanmugam et al, 2008 ). In the current study, the cell-free culture filtrate of T. hamatum at a concentration ranging from 0.5 to 10% markedly inhibited the mycelial growth of L. theobromae , with inhibitory activity increasing with concentration.…”
Section: Resultsmentioning
confidence: 98%
“… Padder and Sharma (2011) reported that culture filtrate of T. hamatum had a significant inhibitory effect on spore germination of Colletotrichum lindemuthianum , and the inhibitory activity of culture filtrates of Trichoderma sp. have also been reported against other fungal pathogens, including Fusarium solani ( Dugassa et al, 2021 ) and F. oxysporum ( Shanmugam et al, 2008 ). In the current study, the cell-free culture filtrate of T. hamatum at a concentration ranging from 0.5 to 10% markedly inhibited the mycelial growth of L. theobromae , with inhibitory activity increasing with concentration.…”
Section: Resultsmentioning
confidence: 98%
“…Several authors have suggested that combinations of introduced microbial agents have to be compatible with each other for better and more consistent disease suppression ( Chien and Huang, 2020 ; Dugassa et al, 2021 ). Bacillus species, particularly B. amyloliquefaciens and B. subtilis , can produce a wide range of antifungal compounds such as lipopeptide antibiotics (e.g., iturin, surfactin, and fengycin) and lytic enzymes (e.g., catalase, protease, and cellulase) ( Xiong et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was shown by the increase of Archaeorhizomyces and Trichoderma while decreasing Ophiosphaerella abundance. In one in vitro study, Trichoderma was seen to inhibit the growth of Fusarium solani, but no inhibition area was observed when it was cultured together with Pseudomonas strains [105]. Trichoderma tends to be compatible and live mutually with beneficial microbes that contribute to plant growth rather than harmful ones.…”
Section: Challenges and Future Prospects For Up-scaling The Use Of Trichoderma For Sustainable Crop Productionmentioning
confidence: 99%